STUDENTS’ PERCEPTIONS ON THE USE OF GOOGLE CLASSROOM TO SUPPORT BLENDED LEARNING FOR THE PENGANTAR LINGUISTIK UMUM COURSE - Todo F. B. Sibuea (LINGUA : JURNAL ILMIAH, 2018)
Implementing blended learning strategy in higher education requires a learning management system (LMS) that is stable, well-proven, and accessible by both teachers and students alike. Google Classroom is an LMS that meets the aforementioned criteria and it has a steady growing acceptance because of its cross-platform presence, stability, and ease-of-use. Though Classroom has gained many users in K-12 environment, it has not gained the same progress in higher education. To investigate whether Classroom can bring positive impact in a higher education course, a research was conducted by utilizing Classroom as an LMS to support blended learning strategy in a Pengantar Linguistik Umum class for a semester. Research participants’ were university students who enrolled in PLU class. Then, the course was conducted by combining face-to-face meeting and online learning facilitated by Google Classroom. Class teacher surveyed students’ knowledge and perceptions about blended learning at the beginning of the course and at the end of semester to investigate their perceptions of using LMS in blended learning environment. The Classroom was used to share video podcasts, online quizzes, and assignments. This research showed that Classroom was a satisfying LMS for blended learning in PLU course because of its features, user-friendliness, and appropriateness in higher education program.